2014
DOI: 10.3389/fpls.2014.00633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proteome rebalancing and sulfur nutrition on the accumulation of methionine rich δ-zein in transgenic soybeans

Abstract: Expression of heterologous methionine-rich proteins to increase the overall sulfur amino acid content of soybean seeds has been only marginally successful, presumably due to low accumulation of transgenes in soybeans or due to gene silencing. Proteome rebalancing of seed proteins has been shown to promote the accumulation of foreign proteins. In this study, we have utilized RNAi technology to suppress the expression of the β-conglycinin, the abundant 7S seed storage proteins of soybean. Western blot and 2D-gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 79 publications
1
28
1
Order By: Relevance
“…Further results were suggestive of a higher methionine concentration in the transgenic line in response to high sulfur and high nitrogen, although this could not be analyzed statistically due to a lack of replication. Recently, Kim et al (2014) reported that adequate sulfate nutrition is required to maximize the accumulation of maize δ-zein in transgenic soybean lines where expression of the endogenous β-conglycinin was suppressed by RNA interference.…”
Section: Discussionmentioning
confidence: 99%
“…Further results were suggestive of a higher methionine concentration in the transgenic line in response to high sulfur and high nitrogen, although this could not be analyzed statistically due to a lack of replication. Recently, Kim et al (2014) reported that adequate sulfate nutrition is required to maximize the accumulation of maize δ-zein in transgenic soybean lines where expression of the endogenous β-conglycinin was suppressed by RNA interference.…”
Section: Discussionmentioning
confidence: 99%
“…The application of glutathione to immature soybean cotyledons reduced the accumulation of the β-subunit of β-conglycinin and increased the accumulation of glycinin (Awazuhara et al, 2002). Further, Kim et al (2014) demonstrated that ample supply of reduced sulphur during seed filling promotes soybean protein quality by reducing the accumulation of sulphur-poor 7S β-conglycinins. Likewise, providing an exogenous source of methionine to soybean plants results in 23 and 31% increase in methionine and cysteine content, respectively (Yi et al, 2010).…”
Section: Resultsmentioning
confidence: 96%
“…During the maturation phase, the production of one storage component likely results from repartitioning of carbon amongst storage reserves. Attempts at rebalancing protein and oil have given mixed results, with strategies to enhance protein such as heterologous protein expression [50] and suppression of specific seed storage proteins [51] providing small gains in the overall protein content due to concurrent changes within the proteome whereas the expression of the Arabidopsis thaliana orphan gene QUA-QUINE STARCH (QQS) in soybean seeds resulted in 4-10% increase in protein predominantly at the expense of starch [52,53]. Conversely, natural variants of RAFFINOSE SYNTHASE responsible for RFO accumulation have decreased RFO content and increased sucrose without further gains in oil or protein accumulation [5].…”
Section: Discussionmentioning
confidence: 99%